The music of Béla Bartók : A study of tonality and progression in twentieth-century music - Antokoletz, Elliott (Berkeley University of California Press, 1990)
The basic principles of progression and the means by which tonality is established in Bartók's music remain problematical to many theorists. Elliott Antokoletz here demonstrates that the remarkable continuity of style in Bartók's evolution is founded upon an all-encompassing system of pitch relations in which one can draw together the diverse pitch formations in his music under one unified set of principles.